Education and the Labor Market : International conference of the German Socio-Economic Panel Study Users (2, 1906, Griebnitzsee/Potsdam) - Burkhauser, Richard V. [Verfasser]; Wasylenko, Michael J. [Verfasser]; Weathers, Robert R. [Verfasser]; Daly, Mary C. [Verfasser]; Büchel, Felix [Verfasser]; Duncan, Greg J. [Verfasser]; Witte, James [Verfasser]; Szydlik, Marc [Verfasser] (My University, 1997)
Auf der Konferenz der Anwender der Ergebnisse des Deutschen Sozio- oekonomischen Panels (SOEP) wurden zum Schwerpunkt "Bildung und Arbeitsmarkt" folgende Beiträge gehalten: BURKHAUSER/WASYLENKO/ WEATHERS: The importance of education on the labor market mobility of prime age males in the United States and Germany in the 1980s; DALY/BÜCHEL/DUNCAN: Premiums and penalties for over- and undereducation cross-time and cross-national comparisons in the United States and Germany; BÜCHEL/WITTE: The incidence and consequences of overeducation among young workers in the United States and Germany; SZYDLIK: Consequences of allocation processes in the labor market : a comparison of the United States and Germany. (BIBB)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 1.3.3.1 Qualifikationsverwertung; G 1.2.2.3 Beschäftigungsformen; I 2.1 Deutschland; I 2.3.2 Nordamerika; Arbeitsmarkt; Ausbildungsabschluss; Einkommen; Qualifikationsverwertung; Überqualifikation; Unterwertige Beschäftigung; Internationaler Vergleich; Quantitative Angaben; 1985-1989